Upgrading of bio-oil from palm empty fruit bunch fibre with non-acidic oxides via catalytic intermediate pyrolysis - Chong, Yen Yee (2020)
In response to the concerns regarding environmental pollution and energy security, renewable energy has been perceived as a solution. As liquid fuel is the most consumed form of energy in the world, much attention has been paid to pyrolysis for the production of bio-oil. Bio-oil may be derived from biomass and is a potential fuel supplement and source of chemicals. However, lignocellulosic biomass-derived bio-oil is generally highly acidic and highly oxygenated than crude oil. Consequently, the bio-oil is unstable and has a comparatively low energy density. Hence, bio-oil has to be upgraded in order to use directly as fuel and other applications. One of the upgrading methods is catalytic pyrolysis using non-acidic oxides.